Structural and functional insights into thermally stable cytochrome c′ from a thermophile. (6th March 2017) - Fujii, Sotaro; Oki, Hiroya; Kawahara, Kazuki; Yamane, Daisuke; Yamanaka, Masaru; Maruno, Takahiro; Kobayashi, Yuji; Masanari, Misa; Wakai, Satoshi; Nishihara, Hirofumi; Ohkubo, Tadayasu; Sambongi, Yoshihiro
Abstract: Thermophilic Hydrogenophilus thermoluteolus cytochrome c ′ (PHCP) exhibits higher thermal stability than a mesophilic counterpart, Allochromatium vinosum cytochrome c ′ (AVCP), which has a homo‐dimeric structure and ligand‐binding ability. To understand the thermal stability mechanism and ligand‐binding ability of the thermally stable PHCP protein, the crystal structure of PHCP was first determined. It formed a homo‐dimeric structure, the main chain root mean square deviation (rmsd) value between PHCP and AVCP being 0.65 Å. In the PHCP structure, six specific residues appeared to strengthen the heme‐related and subunit–subunit interactions, which were not conserved in the AVCP structure. PHCP variants having altered subunit–subunit interactions were more severely destabilized than ones having altered heme‐related interactions. The PHCP structure further revealed a ligand‐binding channel and a penta‐coordinated heme, as observed in the AVCP protein. A spectroscopic study clearly showed that some ligands were bound to the PHCP protein. It is concluded that the dimeric PHCP from the thermophile is effectively stabilized through heme‐related and subunit–subunit interactions with conservation of the ligand‐binding ability. Brief Summary: We report the X‐ray crystal structure of cytochrome c ′ (PHCP) from thermophilic Hydrogenophilus thermoluteolus . The high thermal stability of PHCP was attributed to heme‐related and subunit–subunit interactions, which were confirmed by a mutagenesis study. The ligand‐binding ability of PHCP was examined by spectrophotometry. PHCP acquired the thermal stability with conservation of the ligand‐binding ability. This study furthers the understanding of the stability and function of cytochromes c . Abstract : PDB Code(s):5B3I